The impact of kitten training and socialization classes on cat cognitive bias and discrimination learning - Vitale, Kristyn R.; Master, Champayne D.; Udell, Monique A. R. (Frontiers in Ethology, 2025)
Cats rank among the world’s most popular companion animals. Despite their widespread presence in human homes, accessible training and socialization opportunities for kittens remain scarce. In this study, a 6-week training and socialization class was offered for kittens aged 3-8 months old. Class kittens were compared to a group of control kittens that did not take part in the training and socialization class. Both groups of kittens participated in a cognitive bias test to measure discrimination learning and emotional outlook. Discrimination learning was measured in terms of passing criteria on the cognitive bias test, and the kittens’ responses to an ambiguous stimulus were measured to gauge optimistic or pessimistic outlooks. It was predicted that training and socialization would improve learning and lead to more optimistic judgments in class kittens. Results indicate that the training and socialization class helped maintain the ability to learn the task discrimination over time in class kittens, whereas control kittens that lacked the training and socialization experience displayed a decrease in task discrimination over time (Total N = 63; Experimental = 31, Control = 32). There was no significant difference between the groups in cognitive bias latencies (Total N = 36; Experimental = 17, Control = 19). However, interestingly, both groups showed shorter latency to approach an ambiguous stimulus over time, suggesting a naturally optimistic shift in kittens. This study reports the first use of the cognitive bias test in pet cats, and the findings contribute to our understanding of how socialization and training influence feline cognition and emotional well-being.